Environmental Kuznets Curve: Moderating role of financial development - Mansoor Mushtaq; Shabbir Ahmed (Economic Journal of Emerging Markets, 2021)
Purpose - This study analyzes the moderating role of financial development in the Environmental Kuznets Curve (EKC) hypothesis in 25 countries.Methods - This paper uses Lin and Chu unit root test to check the stationary of the variables. The unit root test result leads to the investigation using the panel pooled mean group model.Findings - The results of the long-run analysis show that the EKC hypothesis exists, and financial development plays its role in two ways. Firstly, it confirms the EKC hypothesis, and secondly, it improves the coefficients of supporting variables, namely economic growth, energy growth, and manufacturing value-added. The results are robust to changing the proxies of dependent as well as independent variables. The error correction model results show that the sign of the error correction term is negative and significant, implying that all of the models will converge toward their long-run equilibrium.Implications - Financial development is a crucial determinant to reduce environmental degradation in these countries. This implies that the governments of these countries should focus on enhancing financial development for the betterment of the environment.Originality - The study analyzes the role of the financial sector as a moderating role in the EKC hypothesis both in emerging economies and well-developed economies.